2020
DOI: 10.3390/foods9101436
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Physicochemical Properties and Metabolite Profiling Using 1H NMR Spectroscopy of Korean Wheat Malt

Abstract: The objective of this study was to compare the physicochemical, enzymatic, and metabolic properties of two control wheat malts imported from Germany and the US to those of malts made from three Korean wheat varieties: Triticumaestivum L., var. Anzunbaengi, Jokyung, and Keumkang. The qualities and enzyme activities of the Korean wheat malts were generally similar to those of the control wheat malts. The Korean wheat malts had slightly lower diastatic power and enzyme activities related to saccharification. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 36 publications
2
4
0
Order By: Relevance
“…For the TN, the Korean wheat malts, KM (2.5%) and AM (2.2%), had significantly (p < 0.05) higher values than the control wheat malts, GB (1.9%) and UB (1.7%). Recently, similar results for Korean wheat malt were reported by Byeon et al [19]. Briefly, the parameters related to nitrogen, such as FAN, SN, TN, and KI, differed between the control wheat malts and the Korean wheat malts.…”
Section: Malt Quality Parameter Analysis For Wheat Maltssupporting
confidence: 82%
See 3 more Smart Citations
“…For the TN, the Korean wheat malts, KM (2.5%) and AM (2.2%), had significantly (p < 0.05) higher values than the control wheat malts, GB (1.9%) and UB (1.7%). Recently, similar results for Korean wheat malt were reported by Byeon et al [19]. Briefly, the parameters related to nitrogen, such as FAN, SN, TN, and KI, differed between the control wheat malts and the Korean wheat malts.…”
Section: Malt Quality Parameter Analysis For Wheat Maltssupporting
confidence: 82%
“…is is probably because KB was made from KM, which had a high methionine concentration. is was confirmed in a previous Korean wheat malt study described by Byeon et al [19], which showed that Keumkang malt had a high methionine content.…”
Section: Volatile Compounds Of Wheat Beersupporting
confidence: 71%
See 2 more Smart Citations
“…In addition, it can be coupled to either gas chromatography (GC) or liquid chromatography (LC), adding another dimension to differentiating the metabolite signals ( Alseekh and Fernie, 2018 ). By employing the above-mentioned technological platforms, one could acquire hundreds of metabolic analytes from wheat samples using the NMR-based ( Byeon et al., 2020 ) or MS-based techniques ( Ameye et al., 2020 ; Wang et al., 2020 ). Although this number is far from covering the whole metabolome of a given species (hundreds detected versus thousands predicted), this is likely reflective of what can be currently achieved in wheat.…”
Section: The Application Of Metabolomics In Wheat Should Deliver the Swift Detection Of A Vast Category Of Metabolitesmentioning
confidence: 99%